Response of steel pipeline crossing strike-slip fault in clayey soils by nonlinear analysis method - Khanbabazadeh, Hadi; Mert, Ahmet Can (Techno-Press, 2023)
Response of the pipeline crossing fault is considered as the large strain problem. Proper estimation of the pipeline response plays important role in mitigation studies. In this study, an advanced continuum modeling including material non -linearity in large strain deformations, hardening/softening soil behavior and soil-pipeline interaction is applied. Through the application of a fully nonlinear analysis based on an explicit finite difference method, the mechanics of the pipeline behavior and its interaction with soil under large strains is presented in more detail. To make the results useful in oil and gas engineering works, a continuous pipeline of two steel grades buried in two clayey soil types with four different crossing angles of 30 & DEG;, 45 & DEG;, 70 & DEG; and 90 & DEG; with respect to the pipeline axis have been considered. The results are presented as the fault movement corresponding to different damage limit states. It was seen that the maximum affected pipeline length is about 20 meters for the studied conditions. Also, the affected length around the fault cutting plane is asymmetric with about 35% and 65% at the fault moving and stationary block, respectively. Local buckling is the dominant damage state for greater crossing angle of 90 & DEG; with the fault displacement varying from 0.4 m to 0.55 m. While the tensile strain limit is the main damage state at the crossing angles of 70 & DEG; and 45 & DEG;, the cross-sectional flattening limit becomes the main damage state at the smaller 30 & DEG; crossing angles. Compared to the stiff clayey soil, the fault movement resulting 3% tensile strain limit reach up to 40% in soft clayey soil. Also, it was seen that the effect of the pipeline internal pressure reaches up to about 40% compared to non-pressurized condition for some cases.
Keywords: buried steel pipes; continuous pipelines; fault crossings; nonlinear soil behavior; soil-pipe interaction; strick-slip fault